Postoperative Long-term Outcomes of Patient with Craniopharyngioma Based on CyberKnife Treatment - Ohhashi, Genichiro (Cureus, 2020)
Objective The results of CyberKnife treatment in patients with craniopharyngiomas are excellent, but reports of long-term follow-up are rare. Hence, considering the possibility of a long-term follow-up of five years or more, we examined the long-term prognoses of these patients. Materials and Methods Of 33 patients, 12 were males and 21 were females. On postoperative evaluation, three patients experienced recurrence after total resection and were treated using CyberKnife. Twenty-five patients were treated with CyberKnife after partial resection. The mean age at treatment was 47 years, and the follow-up period was 61 to 129 months. Results Of the cases assessed as totally resected in the postoperative evaluation, three recurred after 18 months. CyberKnife treatment was administered immediately in recurrent cases; subsequently, no recurrences were observed for 25 months or more. No recurrences were observed in any patients treated with CyberKnife on the residual site after surgical treatment. Many cases had improved pituitary function, but none had deteriorated. In addition, no case of visual function deterioration was reported.  Conclusion Twenty years have passed since the introduction of CyberKnife treatment; however, only a few reports have examined the long-term prognosis of patients with craniopharyngiomas who underwent this treatment. We have been aware of the efficacy of CyberKnife treatment for ten years or more; its long-term results are evident, and the good growth control and low adverse effects are impressive. We are confident that we can maintain good treatment results by combining conservative surgical resection with minimal complications and CyberKnife treatment for new patients in the future.